The influence of quality of adult thorax photos on the satisfaction level of radiology doctors with computed radiography in radiological installation of Panembahan Senopati Hospital Bantul - Asih Puji Utami (International Journal of Health Science and Technology, 2020)
This study aims to determine the effect of adult thorax photo quality on the satisfaction level of Radiology Doctors and to determine the dominant factors that influence the satisfaction level of Radiology Doctors. Type of this research is quantitative with a survey approach. The sample was consisted of 144 thorax photos. Data analysis was carried out descriptively and multiple regression by testing the regression line hypothesis, statistical f test, statistical t test, and coefficient of determination. The results showed that there was an influence on the quality of the radiograph with the Radiology Doctor's satisfaction. The significance value of the density is 0,048, the value of the contrast significance is 0,002, the significance value of sharpness is 0,001 and the value of the detail significance is 0,020. While the dominant factor is the sharpness variable.